A política externa do governo Castello Branco nas atas do Conselho de Segurança Nacional: determinantes domésticos na ação internacional de um ator semiperiférico (1964-1967) - Sion, Vitor Loureiro (2016)
The paper analyzes the foreign policy of Humberto de Alencar Castello Branco government's (1964-1967). From the intersection of the existing literature with the analysis of the minutes of meetings of the National Security Council (CSN), this dissertation discusses the dynamics of the diplomacy of the first government of the military dictatorship. The argument of this paper discusses the interpretation and scope of the automatic alignment of Brazil with the United States between the years 1964 and 1967. Three key aspects support the vision of this work: the pragmatism of Castello Branco´s diplomacy, the predominance of domestic constraints in decision-making and the action of Brazil as a country with semi-peripheral claims to rise in the international system power hierarchy. The study of the content of the CSN´s meetings, which was declassified and went on to be available for research only in 2009, is carried out in order to advance in the opening of the black box of the decision-making process in foreign policy. One of the benefits of the CSN´s minutes analysis is the ability to clearly identify the internal differences in the military dictatorship. Another aspect discussed in the paper is the evolution of Castello Branco's foreign policy, on which it considers that the Institutional Act No. 2 (AI-2), in October 1965, was a turning point. Since then, it is considered that international action of Brazil sought greater autonomy, reducing the dependence on Western superpower